3D PRINTER FEATURES AND TECHNOLOGIES IN A TECHNOLOGY SCHOOL - Evangelista dos Santos, José; Oliveira Borbosa, Luana (Journal of Interdisciplinary Debates, 2025)
This teaching case, developed at a Technical School in Valparaíso de Goiás, Brazil, aims to analyze the integration of 3D printing technology into the technical courses curriculum. The proposal seeks to promote active methodologies, stimulate creativity, collaboration, and problem-solving skills among students. The methodology involved observation of pedagogical practices after the implementation of a maker lab equipped with FDM 3D printers, along with biweekly interdisciplinary planning meetings withteachers. The results revealed both advances and challenges, highlighting the importance of continuous teacher training policies, sustainable management strategies, and the creation of flexible curricular spaces. 3D printing has proven promising for technical education, provided it is supported by pedagogical and institutional backing.